(untitled) (Research, Society and Development, 2020)
At the end of 2019, an infectious disease caused by the severe acute respiratory syndrome coronavirus 2, currently known as COVID-19, appeared in China. Within a globalized society, the worldwide spread of the new and highly contagious coronavirus was inevitable. Until May 7, 2020 Brazil indicated, through an official balance sheet prepared by the Ministry of Health, a number of 9,146 deaths and 135,106 confirmed cases, in addition to an upward curve of the disease. Based on the understanding that any position in the face of this situation can cost lives, this study aims to analyze five speeches by president Jair Messias Bolsonaro in the midst of the pandemic, among them that given during the international delegation in Miami on March 9, the official pronouncement on March 24, and the Easter broadcast on April 12, all of which took place in the year 2020. Thus, this text starts from a historical contextualization about the Spanish flu pandemic, which emerged in 1918 and killed thousands of people in Brazil and worldwide, to analyze an excerpt from the speeches of the President of the Republic during the current pandemic, which occurred approximately one century later. The present article, of a theoretical-analytical nature, was developed from bibliographic reviews and analyzes of Jair Bolsonaro’s speeches propagated through websites, interviews, articles and magazines, that reveal attempts to deny or minimize the risks of the disease.